Singing from manuscripts? Fifteenth-Century, English, secular songs with music and their reading practices - Glover, T (Durham University Department of English Studies, 2017)
This essay explores the reading practices associated with fifteenth-century manuscripts containing English, secular songs with music, of which only two such manuscripts survive. It addresses the claim that the primary mode of reading was one in which readers sang directly from the manuscripts themselves in performance. This essay challenges this claim by exploring the ways in which the manuscripts themselves suggest alternative models of reading and performance. After dissecting previous critical stances on this subject, this essay begins by discussing the construction of the two manuscripts, examining how the varying contexts and purposes which can be inferred suggest very different uses intended for each manuscript, and hence different reading practices. The second section discusses performance contexts in more depth, analysing the ways in which the physical page both facilitates and complicates a performance directly from the manuscript. In particular I explore the ways in which omissions and apparent deficiencies in the music challenge the view that they were intended to be performed from like modern music. In doing so, I attempt to exonerate scribes from the blame laid on them by some music historians, who see these absences as failures rather than as occurring within the context of a more flexible relationship between page and performance than has been previously thought. By exploring the extent to which the manuscripts in fact point to various possibilities of reading, I argue that both manuscripts suggest that they could have been used for a range of functions, including as a book of songs for rehearsal, a memory-aid in performance, or an archival repository of songs. Overall I argue that these books suggest multiple possible modes of reading and performance in relation to the physical page, and hence that the reading practices of fifteenth-century musical manuscripts were more diverse than has previously been suggested.